Penerapan Metode Lean Manufacturing untuk Meningkatkan Efisiensi Produksi pada Industri Manufaktur Skala Menengah - Komarudin, Komarudin (Jurnal Teknik Indonesia, 2025)
Medium-scale manufacturing industries have a significant contribution to national economic growth but still face challenges in production efficiency due to high levels of waste and limitations in process control systems. One proven approach to address these issues is the Lean Manufacturing method. This study aims to analyze the impact of implementing Lean Manufacturing on improving production efficiency in medium-scale manufacturing industries and to identify dominant forms of waste that can be minimized through this approach. This research employs a quantitative approach with a quasi-experimental design, involving measurements of efficiency before and after the implementation of lean through indicators such as lead time, waste, and production output. The data analysis techniques used include descriptive statistical analysis, the Kolmogorov–Smirnov normality test, paired sample t-test, and Value Stream Mapping (VSM). Instrument validity and reliability were tested using Pearson correlation and Cronbach Alpha. The results show a significant increase in production efficiency, from an average of 67.06% before implementation to 86.52% after lean was applied (p < 0.001). Additionally, non-value-added activities were reduced from 45% to 17%, and production cycle time decreased significantly. This study demonstrates that Lean Manufacturing can be effectively adapted for medium-scale industries as a sustainable productivity improvement strategy.